Knowledge and attitudes towards complementary medicine by nursing students at a University in South Africa - Renaldi van Rensburg; Radmila Razlog; Janice Pellow (AOSIS, 2020)
Background: The increased popularity of complementary medicine has created the need for patients to receive accurate information from nurses who are front-line healthcare providers. Studies have demonstrated that patients are more likely to discuss other medication and therapy use with nurses, rather than with general practitioners or other health professionals. It is, therefore, important to determine nurses' knowledge and attitudes towards complementary medicine. Aim: The aim of this study was to determine nursing students' knowledge and attitudes toward the use of complementary medicine. Setting: The study was conducted with Baccalaureus Curationis (nursing) students registered at a large public university in Gauteng, South Africa. Methods: This research utilised a quantitative approach with a prospective, descriptive survey design. A convenience sample comprising registered Baccalaureus Curationis nursing students (n = 202) was utilized. Participants completed a 34-item, paper-and-pencil questionnaire to determine their knowledge, personal use and attitude toward complementary medicine modalities. Results: Questionnaires were completed by 126 nursing students with 119 questionnaires included for analysis. Despite a reported lack of knowledge regarding complementary medicine and limited personal use, participants had an overall positive attitude towards complementary medicine. Almost half of the participants reported enquiring about its use in history taking and were willing to refer patients to a complementary medicine practitioner. Conclusion: A positive attitude towards complementary medicine modalities might suggest a willingness from students to improve their knowledge of the various modalities and to refer to a complementary medicine practitioner when indicated.